2020
DOI: 10.3390/plants9091230
|View full text |Cite
|
Sign up to set email alerts
|

The Common Ice Plant (Mesembryanthemum crystallinum L.)–Phytoremediation Potential for Cadmium and Chromate-Contaminated Soils

Abstract: The common ice plant (Mesembryanthemum crystallinum L.) is a widely studied model due to its tolerance to numerous biotic and abiotic stresses. In this study, carried out in model pots, the plants were treated with variant doses of Cd(II) and Cr(VI) and proved resistant to extreme levels of these heavy metals. Initial toxicity symptoms were observed upon final concentrations of 818 mg Cd kg−1 soil d.w., and 1699 mg Cr kg−1 applied as potassium chromate. Biometric analyses revealed that none of the Cr(VI) doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(91 reference statements)
3
18
0
Order By: Relevance
“…A widely studied model plant Mesembryanthemum crystallinum L. has high tolerance capacity against various biotic and abiotic stresses and it is suitable for bio-reclamation of contaminated soils due to considerable phytoremediation capabilities and unique growth potential. This plant is also especially capable of efficient phytoextraction from chromate-contamination due to its vigorous growth without exhibiting any physiological or anatomical disorders [141]. Thus, it was confirmed that this plant could perform as excellent decontamination for the Cr heavy metal under controlled (pH, redox potential, water disturbances) conditions.…”
Section: Phytostabilization and Phytoextraction For Cr Tolerancementioning
confidence: 69%
“…A widely studied model plant Mesembryanthemum crystallinum L. has high tolerance capacity against various biotic and abiotic stresses and it is suitable for bio-reclamation of contaminated soils due to considerable phytoremediation capabilities and unique growth potential. This plant is also especially capable of efficient phytoextraction from chromate-contamination due to its vigorous growth without exhibiting any physiological or anatomical disorders [141]. Thus, it was confirmed that this plant could perform as excellent decontamination for the Cr heavy metal under controlled (pH, redox potential, water disturbances) conditions.…”
Section: Phytostabilization and Phytoextraction For Cr Tolerancementioning
confidence: 69%
“…Next, the 8-week old plants were treated with CdCl 2 (Sigma-Aldrich, United States) solutions applied at the following concentrations: 0 (control), 0.01, 0.1, 1.0, and 10 mM administered daily as 10 cm 3 doses per pot for consecutive 8 days. This experimental approach was analogous to the model elaborated by us earlier and previously described ( Nosek et al, 2019 , 2020 ; Śliwa-Cebula et al, 2020 ). Such treatment led to the final Cd doses of 0 (control), 0.8, 8.0, 80, and 800 μmol per pot, respectively, which were calculated as 0.82, 8.2, 82, and 818 mg Cd per kg of soil d.w. During the Cd-treatment microbial community frequency and diversity was monitored.…”
Section: Methodsmentioning
confidence: 93%
“…Based on the described extraordinary properties of the common ice plant and considering our recent data on its extreme resistance to cadmium and chromium ( Nosek et al, 2019 ; Śliwa-Cebula et al, 2020 ), we have postulated M. crystallinum as a particularly favorable candidate for environmental biotechnology applications. For the case of heavy metal-contaminated saline areas, halophytes including the common ice plant can serve as potentially efficient phytoremediators ( Wang et al, 2014 ; Lutts and Lefèvre, 2015 ), since plants tend to respond to both heavy metals and salinity by triggering similar physiological and biochemical mechanisms ( Zhu, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations